Update on pathology laboratory development and research in advancing regional cancer care in Malawi - Brownlee, Amy J.; Dewey, Morgan; Chagomerana, Maganizo B.; Tomoka, Tamiwe; Mulenga, Maurice; Khan, Shiraz; Kampani, Coxcilly; Chimzimu, Fred; Gastier-Foster, Julie M.; Westmoreland, Kate D.; Ozuah, Nmazuo W.; Krysiak, Robert; et al. (Frontiers in Medicine, 2024)
The pathology laboratory at Kamuzu Central Hospital (KCH) in Lilongwe, Malawi was established in 2011. We published our initial experiences in laboratory development and telepathology in 2013 and 2016, respectively. The purpose of this paper is to provide an update on our work by highlighting the positive role laboratory development has played in improving regional cancer care and research. In addition, we provide a summary of the adult pathology data from specimens received between July 1, 2011, and May 31, 2019, with an emphasis on malignant diagnoses. We compare these summaries to estimates of cancer incidence in this region to identify gaps and future needs.